Impact of hindcast length on estimates of seasonal climate predictability. Issue 5 (12th March 2015) - Shi, W.; Schaller, N.; MacLeod, D.; Palmer, T. N.; Weisheimer, A.
Abstract: It has recently been argued that single‐model seasonal forecast ensembles are overdispersive, implying that the real world is more predictable than indicated by estimates of so‐called perfect model predictability, particularly over the North Atlantic. However, such estimates are based on relatively short forecast data sets comprising just 20 years of seasonal predictions. Here we study longer 40 year seasonal forecast data sets from multimodel seasonal forecast ensemble projects and show that sampling uncertainty due to the length of the hindcast periods is large. The skill of forecasting the North Atlantic Oscillation during winter varies within the 40 year data sets with high levels of skill found for some subperiods. It is demonstrated that while 20 year estimates of seasonal reliability can show evidence of overdispersive behavior, the 40 year estimates are more stable and show no evidence of overdispersion. Instead, the predominant feature on these longer time scales is underdispersion, particularly in the tropics. Key Points: Predictions can appear overdispersive due to hindcast length sampling error Longer hindcasts are more robust and underdispersive, especially in the tropics Twenty hindcasts are an inadequate sample size to assess seasonal forecast skill